DEVELOPING AN ENGLISH SUPPLEMENTARY COURSEBOOK FOR TENTH GRADERS OF TOURISM STUDENTS - Tery Kusumawardani; Agustinus Ngadiman (Widya Mandala Surabaya Catholic University, 2018)
According to the 2013 Curriculum, English learning materials for both senior high school and vocational high school are equalized. However, it is suggested that the English learning materials for vocational students should be more specific than those for senior high school students because they need to learn specific areas of English in accordance with their major. Finding proper English textbooks for vocational students focusing on their major is not an easy task. In addition, most vocational school teachers also do not have any sufficient time to design the English materials for the vocational students. Therefore, it is recommended to develop the English materials which meet the students’ needs and demands, particularly intended for Tourism Program. In line with those problems, the researcher used ADDIE method which stands for analysis, design, development, implementation, and evaluation as a research design as suggested by Aldobie (2015). Two validators were involved to validate the textbook and they responded positively towards the materials. Furthermore, after using the textbook, three students and a teacher of tourism program were interviewed. They later agreed that the textbook was suitable and was considered to be fun in the learning process.